TECHNOLOGY OF GETTING E-466 FROM PTKTCh AND PAVLONIA AND BANANA CELLULOSES AND ITS PHYSICAL-CHEMICAL, MECHANICAL-STRUCTURAL - Sandybaeva Zamira Hudayberdievna; Murodov Muzaffar Murodovich; Siddikov Abdujalol; Siddikov Murodhodja Abdujalol ugli (Journals Park Publishing, 2022)
A number of practical works have been carried out on the development and research of technology for obtaining E-466 from fibrous waste of ginneries and high-purity cellulose grades obtained on the basis of pavlovnia tree and banana stalks. E-466 cellulose ether, which is the main raw material and secondary product for various industries, is characterized by the fact that it is obtained on the basis of local raw materials.